Design and Control of Temperature and Soil pH for Plants By Notification Thtough Arduino-Uno-Based SMS - Amelia, Nosa Apri (JITCE (Journal of Information Technology and Computer Engineering), 2019)
The design of the control system aims to design a device that can control temperature and pH of the soil for onion plant with notifications via SMS based on Arduino-Uno microcontroller. The method in this study is to test the pH and temperature detected by the pH sensor E201-C and the LM35 sensor and will be forwarded to the microcontroller. The microcontroller will process a comparison of the pH and input temperature values ​​with detected values, if the input pH is small from the detected pH, the microcontroller will activate the relay so that the water pump turns on, if the input pH is greater than the detected pH then the microcontroller activates the relay so the water pump lime is lit, if the input temperature is small than the temperature detected, the microcontroller will activate the relay so that the pure water pump is lit. The results in this study are a device that has been able to control soil pH and temperature for onion plant with a pH range of 5.6 to 7 and temperatures of 250C to 320C. The growth of onions that have been controlled by pH and the soil temperature produce onion plants with a percentage of 78.6 grams of mass and 64 cm diameter percentage while the growth of onion plants which are controlled by the obtained percentage of mass 50.6 grams with a percentage of 38 cm in diameter. Keywords: Arduino-Uno, Water Pump, Relay, Sensor E201-C, LM35 sensor